Dung beetles eat plants : insights into the nutritional world of Euoniticellus intermedius (Reiche) (Coleoptera: Scarabaeinae) - Yates, Megan (Department of Biological Sciences, 2017)
Dung beetle eggs develop within the finite nutritional environment of the brood ball, which is made using maternally processed animal faeces. It is thought that microbial and gut-derived excretions constitute the major source of N and C for adult dung beetles, while developing larvae, which have retained the mouthparts of their saprophagous ancestors, digest larger particles in the brood ball and rely on symbionts present in the brood ball to provide breakdown products for their nutrition. Stable isotope analysis was used to trace the source of developing larval N and C. Nitrogen and carbon contents, as well as C: N ratios, were used to assess the nutritional quality of this finite food source and to track the changes in these values during the course of development. The main source of both larval and adult N and C was plant-derived and preferential assimilation of gut-derived excretions present in the dung did not occur. Symbionts, including fungi, did not appear to play a significant role in larval nutrition. Extensive amino acid recycling occurs during metamorphosis, indicated by the 0.53 %0 enrichment in 815N in emergent beetles. Maternal processing of bulk dung creates an enhanced nutritional environment for offspring and the maternal faecal deposit, on which the egg is positioned, provides the larvae with an initial, nutrient-rich source of food.